Analisis Sistem Pengadaan Kendaraan Dinas Operasional Pemerintah Melalui Sistem Pembelian dan Sewa (Studi Pada Politeknik Negeri Padang) - Santi, Elfitri; Wirahadi, Afridian; Wahyu Saputra, Arif; Mustika, Rasyidah; Ferdawati (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
The official goverment vehicles supply demand the goverment allocate fund in carefully and precise based on the needs. The value of money analysis between buy, rent, and leasing to supplying the official vehicles in Polytechnic State’s of Padang. intent on calculating, analyze, and comparing which alternative that make more value of money between the provisions system of buying, renting and leasing. Methods this Research is Qualitative and The analysis instrument that use in this research is Net Present Value Method also calculating the cost benefit analysis . The research examine 3 type or merk that represent the officeholder vehicles, such as Toyota Hiace Commuter, Kijang Innova V A/T, dan Avanza Veloz. The result of this research indicated that officeholder vehicles supplying system through the buying system is has more benefit that follow by the leasing system and the renting system. This research result could be a reference for Goverment in choosing supplying system of officeholder vehicles in Padang State’s Polytechnic.